LITERASI DIGITAL SEBAGAI UPAYA MENANGKAL HOAKS DI ERA DISRUPSI - Naimatus Tsaniyah; Kannisa Ayu Juliana (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
One of the big problems facing this nation is the spread of hoaxes or fake news. This was triggered partly because of the strengthening of the post truth phenomenon and the ease of disseminating information through social media and conversation applications such as WhatsApp. This study intends to describe the use of digital literacy to counteract hoaxes in the era of disruption. This era was marked by information flooding, rapid and deep-seated changes, and the use of very high internet-based technology. The literature review is used as this research method. The conclusion of this study is that hoaxes can be resisted by developing massive digital literacy skills. Digital literacy skills include eight essential elements: cultural (understanding context), cognitive (expanding mind), constructive (creating positive things), communicative (capable of communicating and networking), confident (confident and responsible), creative (doing new things), critical (critically addressing content), civic (supporting the realization of civil society). The development and strengthening of digital literacy can be done especially in schools, campuses, and other educational institutions.